To Use or Not to Use Metformin in Cerebral Ischemia: A Review of the Application of Metformin in Stroke Rodents - Isaac Arbeláez-Quintero; Mauricio Palacios (Stroke Research and Treatment)
Ischemic strokes are major causes of death and disability. Searching for potential therapeutic strategies to prevent and treat stroke is necessary, given the increase in overall life expectancy. Epidemiological reports indicate that metformin is an oral antidiabetic medication that can reduce the incidence of ischemic events in patients with diabetes mellitus. Its mechanism of action has not been elucidated, but metformin pleiotropic effects involve actions in addition to glycemic control. AMPK activation has been described as one of the pharmacological mechanisms that explain the action of metformin and that lead to neuroprotective effects. Most experiments done in the cerebral ischemia model, via middle cerebral artery occlusion in rodents (MCAO), had positive results favoring metformin’s neuroprotective role and involve several cellular pathways like oxidative stress, endothelial nitric oxide synthase activation, activation of angiogenesis and neurogenesis, autophagia, and apoptosis. We will review the pharmacological properties of metformin and its possible mechanisms that lead to neuroprotection in cerebral ischemia.